Activated Carbon from Cassava Peel as Adsorbent of Lead Metal (Pb2+) in the Water - Anggi Suprabawati; Neng Wiwi Holiyah; Jasmansyah Jasmansyah (Department of Chemistry, Faculty of Sciences and Informatics, Jenderal Achmad Yani University, 2018)
Cassava peels contained carbon elements about 59.31%, it became the base of using cassava peels as activated carbon. One of utilization of activated carbon was adsorption metal lead. Production of activated carbon was conducted in 3 steps were dehydration, carbonation and activation. Study had been conducted by comparing characteristic of activated carbon without activator and activated carbon with variation of KOH concentration as activator were 0.2 M; 0.4 M and 0.6 M so that could be known the optimal KOH concentration. Characteristic testing was conducted for water content, ash content, adsorption of iodium and adsorption of methylene blue also adsorption of lead metal. Measuring of adsorption metal lead was done by Atomic Absorption Spectroscopy. Experiment result shows activated carbon with KOH 0.4 M has best characteristic by water content 3.79%, ash content 8.09%, adsorption of iodium 863 mg/g and adsorption of methylene blue 3116 mg/g also adsorption of metal lead 98%.